EXPRESSION OF ETHNOCULTURAL CONCEPTS IN JAPANESE PHILOSOPHY AND ARTISTIC TEXT - Mamatkulova Kholida Akhtamovna (Journals Park Publishing, 2022)
This paper considers ethnocultural and esthetic concepts. Japanese cultural processes and philosophical views are revealed on the example of the concepts of “wabi”, “sabi”. And also, the significance of ethnocultural concepts in Japanese poetry and theater is laid out.
Keywords: wabi; sabi; yugene